2008
DOI: 10.1111/j.1742-6723.2008.01072.x
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Duret haemorrhages seen on computed tomography

Abstract: We present a case of 80-year-old man who had headache of 1 day duration and gross subdural haemorrhage in the absence of any history of noticeable trauma, leading to descending transtentorial herniation and secondary brain stem haemorrhages called Duret haemorrhages. It is rare to find a Duret haemorrhage on imaging. This case has been presented to highlight the rarity of the condition and the unusual posterior location of the bleed and also the universally fatal nature of these haemorrhages. Relevant literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…In the present case, preoperative CT showed transtentorial herniation, indicating that the blood vessels near the brain stem might be stretched and distorted (7). The decompression was performed with a short time lag between the opening of the anterior and posterior holes.…”
Section: Discussionmentioning
confidence: 52%
“…In the present case, preoperative CT showed transtentorial herniation, indicating that the blood vessels near the brain stem might be stretched and distorted (7). The decompression was performed with a short time lag between the opening of the anterior and posterior holes.…”
Section: Discussionmentioning
confidence: 52%
“…It is suggested that the brainstem hemorrhage is likely due to damaged vessels caused by increased intracranial pressure (ICP). 8,10,13,14 Rapid alleviation of increased ICP, under conditions of elevated blood pressure, could disrupt the small injured vessels, invariably resulting in brainstem hemorrhage. Because of the mass effect caused by CSDH, the blood vessels near the brainstem get stretched and distorted.…”
Section: Discussionmentioning
confidence: 99%
“…3,9,15) The left-sided decompression was performed with short time lag before the right side procedure, which under such conditions might have led to transient aggravation of the right-sided transtentorial herniation by shifting and displacing the brain stem. Consequently, the vessels surrounding the brain stem may have torn, precipitating the hemorrhage into the brain stem.…”
Section: Discussionmentioning
confidence: 99%